(untitled) (Ustozlar uchun, 2025)
Root resorption is the process by which the hard tissues of the tooth and the surrounding bone are destroyed. The frequency of internal resorption is unknown, because the results can vary significantly when using different diagnostic methods. Scientific publications focus on external resorption, but internal resorption is also a problem for the practitioner. This article describes the results of an anonymous survey of doctors in order to analyze knowledge about root resorption and internal resorption, in particular.